Efficacy of ivabradine in patients with poor heart rate control after beta-blocker use in acute myocardial infarction: a pragmatic randomized controlled trial - Li, Yongbin; Ren, Ying; Cheng, Lisong; Zhou, Xin; Li, Wenting; Zhang, Lingli; Cui, Jian; Yao, Zhuhua (Frontiers in Cardiovascular Medicine, 2025)
IntroductionA rapid resting heart rate following acute myocardial infarction (AMI) predicts poor prognosis, making heart rate control crucial in treatment. Ivabradine is commonly used as a second-line therapy when beta-blockers are poorly tolerated. However, its efficacy in improving cardiac function and prognosis compared to beta-blockers alone remains unclear. This study aimed to investigate the efficacy of ivabradine in the “real world” in patients with AMI who exhibited poor heart rate control despite beta-blocker therapy.MethodsA total of 1,632 patients with AMI were screened, and 104 patients with resting heart rate >70 bpm after beta-blocker use were randomized in a 1:1 ratio into two groups: the ivabradine (n = 52) and control groups (n = 52). Metoprolol succinate administration was continued in the control group, whereas the ivabradine group received additional ivabradine administration to achieve a target heart rate <70 bpm. Patients were followed up in outpatient clinics at 3, 6, and 12 months after discharge, during which heart rate, blood pressure, echocardiography, and N-terminal pro-B-type natriuretic peptide (NT-proBNP) were assessed. The primary endpoints were hospitalization for heart failure and cardiovascular death within 12 months. A Cox proportional hazards regression model was used to analyze the risk factors affecting these endpoints.ResultsThere were no statistically significant differences in age, sex, risk factors, cardiac function class, blood pressure, heart rate, and comorbid medications between the two groups at the time of enrollment (P > 0.05). The ivabradine group achieved significantly lower heart rates compared to the control group at the time of discharge and at 3, 6, and 12 months (P < 0.05). At 3 and 6 months after discharge, the Left ventricular ejection fraction (LVEF) in the ivabradine group was higher than in the control group (P < 0.05), and the NT-proBNP level was significantly lower than in the control group (P < 0.05). Kaplan–Meier survival analysis and log-rank test revealed no statistically significant differences in the incidence of hospitalization for heart failure and cardiovascular death between the two groups at 12 months of follow-up (P > 0.05). Cox proportional hazards modeling analysis showed that Killip classification [hazards ratio (HR) = 1.953, 95% confidence interval (CI): 1.207–2.698, P = 0.012] and peak NT-proBNP value during hospitalization (HR = 2.096, 95% CI: 1.117–3.075, P = 0.028) were influencing factors of hospitalization for heart failure. Age (HR = 1.209, 95% CI: 1.132–1.287, P = 0.001), absence of direct percutaneous coronary intervention (HR = 1.095, 95% CI: 1.040–1.149, P = 0.001), and LVEF at discharge (HR = 0.902, 95% CI: 0.807–0.996, P = 0.041) were influential factors for cardiovascular death. Ivabradine use did not significantly reduce the risk of the primary endpoint events (hospitalization for heart failure HR = 1.420, 95% CI: 0.699–2.878, P = 0.332; cardiovascular death HR = 1.025, 95% CI: 0.792–1.257, P = 0.836).DiscussionIn “real-world” patients with AMI and poorly controlled heart rate despite titration of beta-blocker dosing, ivabradine was safe and effective in controlling heart rate and improving LVEF early after discharge. However, it had no effect on the 12-month incidence of hospitalization for heart failure and cardiovascular death after discharge.